2005
DOI: 10.1002/aheh.200400567
|View full text |Cite
|
Sign up to set email alerts
|

Non‐famous Scum Bacteria: Biological Characterization and Troubleshooting

Abstract: Scum biocenoses in activated sludge nutrient removal plants besides “nocardioform actinomycetes” and “Microthrix parvicella” frequently accommodate other conspicuous organisms such as Eikelboom types 0041/0675, 0581, 0092, and 1851, as well as “Nostocoida limicola”‐like organisms. In the scum fraction of high load plants often bacteria of type 1863 and non‐filamentous actinomycetes are found. Many of these morphologically distinguishable scum bacteria are so‐called morphotypes belonging to various groups or ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The Eikelboom Type 0092 ("not famous" bacteria) as one of the dominant species is in agreement with other studies [9,29,33,34]. In particular, the proliferation of this filamentous bacterium was favored by the operating conditions imposed in the IA-MBR and by the lack of dissolved oxygen during the anoxic phases, especially in the Period III.…”
Section: Filamentous Bacteria In Ia-mbrsupporting
confidence: 90%
“…The Eikelboom Type 0092 ("not famous" bacteria) as one of the dominant species is in agreement with other studies [9,29,33,34]. In particular, the proliferation of this filamentous bacterium was favored by the operating conditions imposed in the IA-MBR and by the lack of dissolved oxygen during the anoxic phases, especially in the Period III.…”
Section: Filamentous Bacteria In Ia-mbrsupporting
confidence: 90%
“…The screening of the biocenoses (for details see [18]) from 40 different WWTPs (38 municipal and two industrial WWTPs) with scum formation revealed in 98 % of all cases "M. parvicella" to occur in activated sludge. However, only in 50 % of the examined plants "M. parvicella" was the dominant filament in both activated sludge and scum.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2, the E. type 0092 and E. type 1851 are the morphotypes that dominated the biocenosis of biological foam in the examined cases even though they are considered "non-famous" scum bacteria (Lemmer et al, 2005). On the other hand, the quantities of other well-known, foam-forming bacteria, e.g., M. parvicella, Nocardioform, and Nostocoida limicola III were negligible.…”
Section: Role Of Filamentous Bacteria In Foaming In An Mbrmentioning
confidence: 92%